2020
DOI: 10.1177/0960327120961158
|View full text |Cite
|
Sign up to set email alerts
|

The cross-talk of NLRP3 inflammasome activation and necroptotic hepatocyte death in acetaminophen-induced mice acute liver injury

Abstract: Overdose acetaminophen (APAP) can result in severe liver injury, which is responsible for nearly half of drug-induced liver injury in western countries. Previous studies have found that there existed massive hepatocellular necrosis and severe inflammatory response in APAP-induced liver injury. However, the mechanistic linkage between necroptosis and NLRP3 inflammasome pathway in APAP-induced hepatotoxicity remains poorly understood. In order to investigate the relationship between inflammation and hepatocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Necrotic hepatocytes release damage-associated molecular patterns (DAMPs) that activate the NLR family pyrin domain containing 3 (NLRP3) inflammasome, which cleaves procaspase-1, forming active caspase-1 (Roh and Sohn 2018 ; Li et al 2021 ). Caspase-1 then cleaves pro-interleukin-1 beta (pro-IL-1β), forming active IL-1β, which triggers the recruitment of neutrophils and monocytes to the liver (Woolbright and Jaeschke 2017 ; Li et al 2021 ; Seok et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Necrotic hepatocytes release damage-associated molecular patterns (DAMPs) that activate the NLR family pyrin domain containing 3 (NLRP3) inflammasome, which cleaves procaspase-1, forming active caspase-1 (Roh and Sohn 2018 ; Li et al 2021 ). Caspase-1 then cleaves pro-interleukin-1 beta (pro-IL-1β), forming active IL-1β, which triggers the recruitment of neutrophils and monocytes to the liver (Woolbright and Jaeschke 2017 ; Li et al 2021 ; Seok et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research reported that the expression of critical molecules in NLRP3 inflammasome was significantly higher in APAP‐treated mice than in control mice, and this difference disappeared following inhibition of necroptosis with Nec‐1. In addition, further investigation indicated that the level of IL‐1β in mouse liver was closely consistent with the level of p‐MLKL in response to APAP exposure, as evidenced by co‐localization of p‐MLKL and IL‐1β 74 . Tao's study demonstrated that RIPK1 activity was promoted in hepatic macrophages after HFD feeding, but hepatic inflammation was obviously alleviated in RIPK1 kinase‐dead (RIPK1 K45A/K45A ) mice compared with WT mice, implying that RIPK1 is required for controlling hepatic macrophage infiltration and activation 75 .…”
Section: Crosstalk Between Necroptosis and Other Ald‐associated Patho...mentioning
confidence: 60%
“…In addition, further investigation indicated that the level of IL‐1β in mouse liver was closely consistent with the level of p‐MLKL in response to APAP exposure, as evidenced by co‐localization of p‐MLKL and IL‐1β. 74 Tao's study demonstrated that RIPK1 activity was promoted in hepatic macrophages after HFD feeding, but hepatic inflammation was obviously alleviated in RIPK1 kinase‐dead (RIPK1 K45A/K45A ) mice compared with WT mice, implying that RIPK1 is required for controlling hepatic macrophage infiltration and activation. 75 Also, the results obtained in both bone marrow–derived macrophages (BMDMs) and primary Kupffer cells (KCs) further confirmed the hypothesis that RIPK1 plays a crucial role in mediating inflammasome activity.…”
Section: Crosstalk Between Necroptosis and Other Ald‐associated Patho...mentioning
confidence: 99%
“…In the liver, activated KCs stimulate NLRP3, which results in a wide range of immune responses including production of pro-inflammatory cytokines and chemokines that subsequently induce cell death [ 127 ]. NLRP3 initiates inflammation, leading to tissue damage and fibrosis in various conditions including alcoholic steatohepatitis, DILI, and NASH, through IL-17 and TNF-α [ 128 ]. NLRP3 mutant mice have been shown to have higher expression of these cytokines that were mainly produced by the infiltrating cells.…”
Section: Role Of Inflammasomes In Hepatic Fibrosismentioning
confidence: 99%